Scott the Rhymer - Goslee, Nancy Moore, 1941- (Book collections on Project MUSE., 2015)
Renewed arguments over the definition of Romanticism warrant a new look at the narrative poetry of Sir Walter Scott. Nancy Moore Goslee's study, the first full treatment of Scott's poems in many years, will do for his poetry what Judith Wilt's book has done for his novels. Already a subtle reader of the high Romantics and their celebrations of the visionary imagination, Goslee draws upon several recent critical developments for this study of Scott: a growing tendency among critics of his novels to see romance as a positive strength, the broader development of narrative theory, and feminist the.